The Effect of Reciprocal Teaching Learning Model on Student Learning Outcomes - Muh Anas; Warda Murti; Nana Erna; Muqtakdir Nurfalaq Syarif (Jurnal Pendidikan Biologi, 2022)
The learning process is important because human learning can add and update knowledge that is useful for the future. Science is growing from age to age, so the learning process will develop and the learning methods will be more varied. One of the learning methods that can be applied is the method reciprocal teaching which is one of the effective methods because it trains students' process skills. This study aims to see how the effect of using the method on student learning outcomes, this type of research is pre-experimental research by giving pretest and posttest treatments to one experimental class. The sample of this research is Biology Education students of FKIP UMMA in the Basic Microbiology course program with a total of 26 students consisting of 13 male students and 13 female students where the sampling method used is Purposive Sampling. One experimental class was taught using the Reciprocal Teaching learning method. The research instrument used was a multiple choice test of 20 items which had been validated by two experts, namely content and language experts. The research data were analyzed descriptively and inferentially. The results of this study indicate that there is a higher effect on student learning outcomes who are taught by learning using the reciprocal teaching model than before being given the treatment. These differences indicate that the reciprocal teaching model is an effective learning method used in these subjects because this learning model trains students to be more active and enthusiastic in the learning process.